Control functions of the judiciary in the Republic of Kazakhstan: the nature, specificity, prospects (Journal of actual problems of jurisprudence, 2018)
Judicial review is a control function of the state, sold by the judiciary. The constitutional function of the judicial power is concentrated in a judicial mechanism to protect the rights and freedoms of the individual, the restoration of violated or disputed rights and interests of the individual. In a state of law the court finds particularly important in the mechanism of government, elevated to the rank of subjects of control, ensuring its legitimacy. Self-sufficiency, independence of the judiciary is a sign of civil society, the formation of which represents one of the most urgent challenges of our time.Key words: protection of the rights and freedoms of the individual, the judiciary, control functions, state control, judicial review, constitutional category, features, classification of judicial review. Modernization as a factor in increasing the efficiency of state financial control.